Creating contexts for effective homebased care of people living with HIV/AIDS - C. Campbell; C. Foulis (AOSIS, 2004)
Home-based care (HBC) plays a vital role in the care of people living with AIDS. Most carers perform their arduous role in adverse conditions. Yet little is known about how to facilitate contexts that maximise the effectiveness of carers. This paper reviews existing research into home-based care in sub-Saharan Africa to highlight gaps in understanding and to outline new conceptual frameworks for future research. Current research identifies multi-level factors that undermine carers in performing their role. These include e.g. lack of knowledge, skills and support - both at the individual and organisational levels; physical and psychological burnout; the destruction of household economies in the face of the demands of care; community stigma and rejection. Research and policy documents repeatedly advocate 'partnerships' or 'linkages' between carers/ patients and more powerful groupings (locally, nationally and/or internationally) as a solution to these problems. Yet they give no indication as how best to mobilise already over-burdened carers and their terminally ill charges. Furthermore, partnerships between poor communities and more influential groupings and agencies are notoriously difficult to promote and sustain. If partnerships are indeed to play such a key role in supporting carers and their patients, there is an urgent need for systematic research into the effectiveness of various partnership styles and strategies. The concepts of bonding, bridging and linking social capital - within a framework sensitive to the interaction between social capital and poverty - are put forward as a valuable starting point for the development of better understandings of the types of networks and partnerships most likely to support carers and their local communities.